HUBUNGAN KEKUATAN OTOT LENGAN TERHADAP KETEPATAN HASIL SHOOTING PADA UKM PETANQUE UIR - Alpen, Joni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to determine the strength of the arm muscles on the accuracy of shooting results at UKM Petanque UIR. This type of research is correlation research. The sample of this study were 14 people taken from the total athletes of UKM Petanque UIR. This study has 2 variables, namely arm muscle strength and Petanque shotting results. The instruments of these 2 variables include push ups and shooting petanque results. Based on the results of the research that has been done, the results of the calculations that have been carried out are the value of r count greater than r table or 0.606 > 0.53, meaning that there is a variable between arm muscle strength and the results of the Petanque shotting. The contribution of arm muscle strength to shooting accuracy is 36%, while the rest is influenced by other factors such as endurance, leg muscle strength, and other physical conditions in Petanque sports.